Dynamic changes of phenolic acids and antioxidant activity of Citri Reticulatae Pericarpium during aging processes. (30th March 2022) - Bian, Xiqing; Xie, Xinyi; Cai, Jialing; Zhao, Yiran; Miao, Wen; Chen, Xiaolin; Xiao, Ying; Li, Na; Wu, Jian-Lin
Graphical abstract: Highlights: The dynamic changes of components in CRP were profiled and investigated. Phenolic acids were the main increased components in CRP during storages. 39 phenolic acids were reported in CRP for the first time. Phenolic acids were quantified and correlation with antioxidant activity were analyzed. Phenolic acids are the possible indicators that long storage would improve CRP quality. Abstract: Citri reticulatae pericarpium (CRP) shows multiple bioactivities, including antioxidant, anti-tumor, and anti-inflammation. The folk proverb "CRP, the older, the better" means storing for longer time would improve its quality, which attributed to the influence of bioactive compounds. The aim of this work was to study which compounds are the factors that long storage would influence the quality of CRP. 161 compounds, including 65 flavonoids, 51 phenolic acids, 27 fatty acids, and 18 amino acids were identified through derivatization and non-derivatization liquid chromatography mass spectrometry approaches. Their dynamic changes indicated phenolic acids, which were reported to have various activities, were the main increased components. Furthermore, the representative phenolic acids were quantified and correlation analysis between their contents and antioxidant activity implicated they were the possible indicators that long storage would improve CRP quality. The results would provide basis for quality control of CRP during storage.